2014
DOI: 10.1161/strokeaha.114.005888
|View full text |Cite
|
Sign up to set email alerts
|

Postischemic Reperfusion Causes Smooth Muscle Calcium Sensitization and Vasoconstriction of Parenchymal Arterioles

Abstract: Background and Purpose Parenchymal arterioles (PAs) are high resistance vessels in the brain that connect pial vessels to the microcirculation. We previously showed that PAs have increased vasoconstriction after ischemia and reperfusion that could increase perfusion deficit. Here, we investigated underlying mechanisms by which early post-ischemic reperfusion causes increased vasoconstriction of PAs. Methods Isolated and pressurized PAs from within the MCA territory were studied in male Wistar rats that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 40 publications
(51 reference statements)
4
69
0
Order By: Relevance
“…Parenchymal arterioles develop substantial myogenic tone 26-28 and are key contributors to overall cerebral vascular resistance 29 . In the current study, parenchymal arterioles generated spontaneous tone once pressurized (37.1±3.0% of maximum diameter; n=10 arterioles) to a baseline diameter of 17±2 μm (active diameter).…”
Section: Resultsmentioning
confidence: 99%
“…Parenchymal arterioles develop substantial myogenic tone 26-28 and are key contributors to overall cerebral vascular resistance 29 . In the current study, parenchymal arterioles generated spontaneous tone once pressurized (37.1±3.0% of maximum diameter; n=10 arterioles) to a baseline diameter of 17±2 μm (active diameter).…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that the large network of capillaries is not the site of greatest resistance to flow in the brain and therefore targeting capillary reductions in flow may not be as beneficial as targeting upstream parenchymal arterioles that are high resistance and the bottleneck to flow to the brain parenchyma [60-62]. In fact, studies have shown that parenchymal arterioles undergo vasoconstriction in response to early post-ischemic reperfusion, a time period important for preventing infarct expansion [63]. …”
Section: Targeting Recanalization and Reperfusion As A Neuroprotectivmentioning
confidence: 99%
“…Parenchymal arterioles undergo vasoconstriction in response to early post-ischemic reperfusion due to calcium sensitization of the vascular smooth muscle [63]. Parenchymal arterioles are unique vessels in the brain and have greater tone at lower pressures than pial arteries due to a lack of influence of the large-conductance calcium-activated potassium (BK) channel [64].…”
Section: Targeting Recanalization and Reperfusion As A Neuroprotectivmentioning
confidence: 99%
See 2 more Smart Citations